Management of hepatic vein occlusive disease after liver transplantation: A case report with literature review. Issue 24 (June 2018) - Hou, Yuchen; Tam, Nga Lei; Xue, Zhicheng; Zhang, Xuzhi; Liao, Bing; Yang, Jie; Fu, Shunjun; Ma, Yi; Wu, Linwei; He, Xiaoshun
Abstract: Rationale: Hepatic vein occlusive disease (HVOD) is a rare complication after liver transplantation, which is characterized by nonthrombotic, fibrous obliteration of the small centrilobular hepatic veins by connective tissue and centrilobular necrosis in zone 3 of the acini. HVOD after solid organ transplantation has been reported; recently, most of these reports with limited cases have documented that acute cell rejection and immunosuppressive agents are the major causative factors. HVOD is relatively a rare complication of liver transplantation with the incidence of approximately 2%. Patient concerns: A 59-year-old male patient with alcoholic liver cirrhosis underwent liver transplantation in our center. He suffered ascites, renal impairment 3 months after the surgery while liver enzymes were in normal range. Diagnoses: Imagining and pathology showed no evidence of rejection or vessels complications. HVOD was diagnosed with pathology biopsy. Interventions: Tacrolimus was withdrawn and the progression of HVOD was reversed. Outcomes: Now, this patient has been followed up for 6 months after discharge with normal liver graft function. Lessons: The use of tacrolimus in patients after liver transplantation may cause HVOD. Patients with jaundice, body weight gain, and refractory ascites should be strongly suspected of tacrolimus related HVOD.